The Impact of Influenza and Tuberculosis Interaction on Mortality Among Individuals Aged ≥15 Years Hospitalized With Severe Respiratory Illness in South Africa, 2010–2016. (19th March 2019) - Walaza, Sibongile; Tempia, Stefano; Dawood, Halima; Variava, Ebrahim; Wolter, Nicole; Dreyer, Andries; Moyes, Jocelyn; Von Mollendorf, Claire; McMorrow, Meredith; Von Gottberg, Anne; Haffejee, Sumayya; Venter, Marietje; et al.
Abstract: Background: Data on the prevalence and impact of influenza–tuberculosis coinfection on clinical outcomes from high–HIV and –tuberculosis burden settings are limited. We explored the impact of influenza and tuberculosis coinfection on mortality among hospitalized adults with lower respiratory tract infection (LRTI). Methods: We enrolled patients aged ≥15 years admitted with physician-diagnosed LRTI or suspected tuberculosis at 2 hospitals in South Africa from 2010 to 2016. Combined nasopharyngeal and oropharyngeal swabs were tested for influenza and 8 other respiratory viruses. Tuberculosis testing of sputum included smear microscopy, culture, and/or Xpert MTB/Rif. Results: Among 6228 enrolled individuals, 4253 (68%) were tested for both influenza and tuberculosis. Of these, the detection rate was 6% (239/4253) for influenza, 26% (1092/4253) for tuberculosis, and 77% (3113/4053) for HIV. One percent (42/4253) tested positive for both influenza and tuberculosis. On multivariable analysis, among tuberculosis-positive patients, factors independently associated with death were age group ≥65 years compared with 15–24 years (adjusted odds ratio [aOR], 3.6; 95% confidence interval [CI], 1.2–11.0) and influenza coinfection (aOR, 2.3; 95% CI, 1.02–5.2). Among influenza-positive patients, laboratory-confirmed tuberculosis was associated with an increased risk of death (aOR, 4.5; 95% CI, 1.5–13.3). Coinfection with other respiratory viruses was not associated with increased mortality in patients positive for tuberculosis (OR, 0.7; 95% CI, 0.4–1.1) or influenza (OR, 1.6; 95% CI, 0.4–5.6). Conclusions: Tuberculosis coinfection is associated with increased mortality in individuals with influenza, and influenza coinfection is associated with increased mortality in individuals with tuberculosis. These data may inform prioritization of influenza vaccines or antivirals for tuberculosis patients and inform tuberculosis testing guidelines for patients with influenza.